Efektivnost indikátoru MACD na akciích společnosti ČEZ - Pavel Fuksa; Milan Svoboda (Trendy v podnikání, 2016)
This paper deals with efficiency of the MACD indicator. The aim of the study is to find whether this indicator would be usable for creating a business strategy for active trading at a stock exchange. The research was carried out on the basis of day closing share prices of the company CEZ, traded on the Prague stock exchange, during the ten-year period from 2006 to 2016. The MACD indicator was calculated in three slightly modified methods. The first method was based on the crossing of MACD and signal line, the second method was similar but reliant on oscillation line. The last method was based on the crossing of MACD and oscillation line. All these methods were calculated in three time periods (short-term, medium-term and long-term). None of the MACD methods beat passive strategy “buy-and-hold” in short-term period. However, for the medium-term and long-term periods, in four of six cases the MACD methods were better then the buy-and-hold strategy. Especially the third method shows very promising results. This study could be used as a building block for further research.